Distribution patterns for megabenthos in the Alekseev Bay (Amur Bay, Japan Sea) - R. V. Vlasenko; D. A. Sokolenko (Известия ТИНРО, 2025)
Species composition and abundance of megazoobenthos is considered on results of SCUBA survey in the Alekseev Bay conducted in 2017. Six groupings of megabenthos are determined within the bay. The stock of megabenthos and general patterns of its biomass spatial distribution did not change much over the past 50 years, but some changes are detected for the boundaries of biotic groupings and their quantitative species composition. Filtering sestonophages, as mussel Crenomytilus grayanus and horsemussel Modiolus kurilensis, still dominated, but the latter became more abundant and wider distributed. Sea urchins Mesocentrotus nudus and Strongylocentrotus intermedius, yesso scallop Mizuhopecten yessoensis and japanese spiky sea cucumber Apostichopus japonicus became less abundant; sea peach Halocynthia aurantium, rather common previously, became rare in the benthic fauna and did not longer form a separate grouping. On the contrary, a new grouping appeared formed by oyster Crassostrea gigas and mussel Crenomytilus grayanus. Possible causes of the occurred changes are discussed.